2006
DOI: 10.1080/13284200600690461
|View full text |Cite
|
Sign up to set email alerts
|

Overview and analysis of the behaviourist criticism of theDiagnostic and Statistical Manual of Mental Disorders(DSM)

Abstract: While a majority of cognitive behavioural researchers and clinicians adhere to the classification system provided in the Diagnostic and Statistical Manual of Mental Disorders (DSM‐IV), strong objections have been voiced among behaviourists who find the dichotomous allocation of patients into psychiatric diagnoses incompatible with the philosophy of behaviourism and practice of functional analysis. The aim of this paper is to give an overview of the current debate and to analyse the tension between the DSM‐IV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…An important question is whether dependence is a discrete, dichotomous state that is either present or absent, or a continuum that can vary quantitatively. Psychiatric diagnosis treats all disorders as dichotomous ( American Psychiatric Association [APA], 2000 ) and has been criticized for ignoring intermediate variations ( Andersson & Ghaderi, 2006 ;Baker, Breslau, Covey, & Shiffman, 2012 ). Similarly, the Hooked on Nicotine Checklist ( HONC ;DiFranza et al, 2002 ) is typically scored dichotomously, considering endorsement of even one symptom as an indication of dependence and has similarly been criticized for classifying almost all smokers (and even some nonsmokers; Dar & Frenk, 2010 ;Hughes & Shiffman, 2008 ) as dependent.…”
Section: Introductionmentioning
confidence: 99%
“…An important question is whether dependence is a discrete, dichotomous state that is either present or absent, or a continuum that can vary quantitatively. Psychiatric diagnosis treats all disorders as dichotomous ( American Psychiatric Association [APA], 2000 ) and has been criticized for ignoring intermediate variations ( Andersson & Ghaderi, 2006 ;Baker, Breslau, Covey, & Shiffman, 2012 ). Similarly, the Hooked on Nicotine Checklist ( HONC ;DiFranza et al, 2002 ) is typically scored dichotomously, considering endorsement of even one symptom as an indication of dependence and has similarly been criticized for classifying almost all smokers (and even some nonsmokers; Dar & Frenk, 2010 ;Hughes & Shiffman, 2008 ) as dependent.…”
Section: Introductionmentioning
confidence: 99%
“…This ‘nosology of diseases’ [21] based not on empirical evidence, but on clinical authority and historical tradition [22], has been problematic for psychiatry itself [13, 23–26], let alone for clinical psychology. It has been plagued by such major problems as excessive rates of comorbidity [27, 28], which may be an indicator of arbitrary boundaries between its disorders [29, 30], by the broad heterogeneity within its diagnosed groups [21, 3133], and by the fact that none of the putative underlying disease processes have been uncovered in the 35 years of research since DSM-III was published [25, 34–37]. The search for biological etiology has greatly disappointed [38, 39], suggesting that psychiatric diagnosis has over simplified psychopathology [40].…”
Section: The Need For a New Conception Of Clinical Psychological Probmentioning
confidence: 99%
“…While many medical diagnoses point to underlying biochemical or neurological mechanisms, few psychopathological ones do [2325]. Neither do they indicate particular psychological-level mechanisms [34, 35]. Hence, clinical psychologists rarely find such diagnoses useful.…”
Section: Seeking the Essence Of Clinical Psychological Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative strengths and weaknesses of DSMtype psychiatric diagnosis versus behavioural functional analysis or cognitive behavioural case formulation have been thoroughly summarised by Andersson and Ghaderi (2006). They concluded that, although the DSM system has failed in providing therapeutic guidelines, functional analysis has thus far failed to provide a functional classification system.…”
Section: Pmc-based Diagnosismentioning
confidence: 99%